Stem Cells and Herbal Acupuncture Therapy - Ki Rok Kwon (Korean Pharmacopuncture Institute, 2005)
Stem cell therapy implies the birth of regenerative medicine. Regenerative medicine signify treatment through regeneration of cells which was impossible by existing medicine. Stem cell is classified into embryonic stem cell and adult stem cell and they have distinctive benefits and limitations. Researches on stem cell are already under active progression and is expected to be commercially available in the near future. One may not relate the stem cell treatment with Oriental medicine, but can be interpreted as the fundamental treatment action of Oriental medicine is being investigated in more concrete manner. When it comes to difficult to cure diseases, there is no boundary between eastern and western medicine, and one must be ready to face and overcome changes lying ahead.